Developing Game Profiling Framework To Generate Gamification & Communication - Prasetyo, Lusi Noviani; Gamayanto , Indra (Jurnal Audience: Jurnal Ilmu Komunikasi, 2024)
Game is a means in shaping character, Creativity and communication. Therefore, games cannot separate in our lives because games are one of the most important parts and have an important role in developing competence. This research is a development of two previous types of research that have obtained patents: Benthix VR: a virtual reality simulation application to preserve a traditional game & to develop a techno-family through virtual-reality benthix game. This development resulted in a game profiling framework that guides building games more systematically and structured manner. However, problems such as the game's function not yet maximized and the response that games are more likely to have disruptive factors in the learning process are factors that this research will overcome. Therefore, this research will produce a game profiling framework called the trilogy of game profiling. The trilogy of game profiling produces the seven stages of educational games and gamification. Furthermore, this research will explain the concept, case study and application of the seven stages of the educational game, which consists of: see, discussion, establish, build, define, decide, and expand (implementation), to produce special gamification of the learning process at the educational level. This research will continue in the next stage, which will discuss gamification in detail, prototyping and application development in the context and content. Keywords: Concepts; Gamification & communication; Implementation; The seven stages of educational game; The trilogy of game profiling